RANCANGAN CREATIVE HUB DI BANJARBARU - Firdaus, Muhammad Adrian; Muchamad, Bani Noor (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Indonesia is experiencing rapid growth in the creative industry, especially in the digital sector. The city of Banjarbaru shows potential as a center for digital creative industries. However, the lack of facilities is still an obstacle. This article discusses the problem: designing a Creative Hub that supports collaboration in the digital creative industry. Using the Blurring Architecture method, which eliminates the boundaries between space and activity, creates flexible space. The history of the Creative Hub shows the importance of this concept in supporting the creative economy and community. This proposes an architectural solution to support the growth of the creative industry in Banjarbaru through a Creative Hub that adopts Blurring Architecture, enabling collaboration and innovation, maximizing the creative potential of Indonesia's young generation.